A one month high fat diet disrupts the gut microbiome and integrity of the colon inducing adiposity and behavioral despair in male Sprague Dawley rats - Gladys Chompre; Lubriel Sambolin; Myrella L. Cruz; Rafael Sanchez; Yarelis Rodriguez; Ronald E. Rodríguez-Santiago; Yasuhiro Yamamura; Caroline B. Appleyard (Heliyon, 2022)
High-fat diet (HFD) is associated with gut microbiome dysfunction and mental disorders. However, the time-dependence as to when this occurs is unclear. We hypothesized that a short-term HFD causes colonic tissue integrity changes resulting in behavioral changes. Rats were fed HFD or low-fat diet (LFD) for a month and gut microbiome, colon, and behavior were evaluated. Behavioral despair was found in the HFD group. Although obesity was absent, the HFD group showed increased percent weight gain, epididymal fat tissue, and leptin expression. Moreover, the HFD group had increased colonic damage, decreased expression of the tight junction proteins, and higher lipopolysaccharides (LPS) in serum. Metagenomic analysis revealed that the HFD group had more Bacteroides and less S24-7 which correlated with the decreased claudin-5. Finally, HFD group showed an increase of microglia percent area, increased astrocytic projections, and decreased phospho-mTOR. In conclusion, HFD consumption in a short period is still sufficient to disrupt gut integrity resulting in LPS infiltration, alterations in the brain, and behavioral despair even in the absence of obesity.